Obtaining arabinogalactan-contained complexes with anthocyanins and betanin antioxidants - Гураль, Лариса Сергіївна (Technology audit and production reserves, 2015)
The conditions of anthocyanins and betanin complex formation by arabinogalactan were investigated. It was established that the greatest degree of binding of biologically active compounds from biopolymer matrix occurs when the combination of their 0,1 % aqueous solutions in volumetric ratios is 1:1. Complex with betanin formed at a temperature 18-22 °C, complex with anthocyanins – at a temperature 40-45 °C. The formation of the complex of betanin and anthocyans with arabinogalactan is proven with methods using gel chromatography, UV and IR spectroscopy and derivatography. The complex formation of low-molecular biologically active compounds with biopolymers accompanied by a change in their UV and IR spectra compared to the individual components. According to differential IR spectroscopy, formation of stable complexes is provided by hydrogen bonds between the interacting components. According to derivatography, destruction of these bonds is in a low-temperature range, degradation of biopolymer components takes place at a much higher temperature. pH and thermal stability of immobilized betanin and anthocyanins are increased as a result of the complex formation. Immobilization in arabinogalactan contributes to the preservation of their biological effects: antioxidant activity in the composition of complexes increases compared with free betanin and anthocyanins. The obtained complexes are polyfunctional high active physiologically functional food ingredients.